If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2f = 3 Solving 5 + -2f = 3 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2f = 3 + -5 Combine like terms: 5 + -5 = 0 0 + -2f = 3 + -5 -2f = 3 + -5 Combine like terms: 3 + -5 = -2 -2f = -2 Divide each side by '-2'. f = 1 Simplifying f = 1
| 25=5/2x+20 | | 3x+(4x-42)=21 | | 9x=36-3x | | x^2-2x+7=10 | | 6x-21=4x-1 | | (45x/5)=36 | | 3x+13=87-7x | | (4y-5)(2y-5y+3)= | | 10-x=3+12 | | (x/5)+9=36 | | 4x+3=6x-15 | | 9r/2r= | | 2b+7=17 | | 6+1/5h=10 | | (y/3)-6=13 | | x/2+1=3x+2 | | 160x=1924801 | | 6x+2+9x+1+5x-3+x=360 | | 7x-12=x+6 | | 71-3x=6x+23 | | 96+x=300 | | 8y=48-4y | | 5p-4p=3p+8 | | 5-x=2(x-3)+5 | | 35y-5(y+9)=15 | | (x-4)(x+2)(x+9)=0 | | 4x-8=2x-12 | | 9x=10+12 | | 2ab=8 | | 92-4x=2x+8 | | 93+89+134+92+x=540 | | 3x/10-4=14 |